Applying the 2019 European Alliance of Associations for Rheumatology/American College of Rheumatology Lupus Criteria to Patients From the LUMINA Cohort: Results From the Multiethnic, Multicenter US Cohort. Issue 10 (1st September 2021) - Ugarte‐Gil, Manuel F.; Pons‐Estel, Guillermo J.; Harvey, Guillermina B.; Vilá, Luis M.; Griffin, Russell; Alarcón, Graciela S.
Abstract : Objective: To evaluate the performance of the 2019 European Alliance of Associations for Rheumatology (EULAR)/American College of Rheumatology (ACR) criteria for systemic lupus erythematosus (SLE) in terms of earlier SLE classification in comparison to the ACR or the Systemic Lupus International Collaborating Clinics (SLICC) criteria. Methods: Patients from a multiethnic, multicenter cohort, the Lupus in Minorities: Nature versus Nurture cohort, where SLE was defined using the 1982/1997 ACR criteria were included. Demographic, clinical, and immunologic criteria were compared among the 2019 EULAR/ACR and the 1982/1997 ACR and the 2012 SLICC timing categories. Results: The 2019 EULAR/ACR criteria allowed an earlier SLE classification in 13.3% of patients (mean 0.66 years) and 15.3% of patients (mean 0.63 years) compared to the 1982/1997 ACR and the 2012 SLICC criteria, respectively. Patients accruing the 2019 EULAR/ACR criteria later than the 1982/1997 ACR criteria had a lower disease activity, were less likely to have positivity to anti–double‐stranded DNA and anti‐Sm, as well as lupus nephritis classes II or V; they were more likely to have mucocutaneous manifestations, serositis, leukopenia, and antiphospholipid antibodies positivity. These differences were less pronounced when compared to the 2012 SLICC criteria Conclusion: The 2019 EULAR/ACR criteria classified SLE patients earlier than the 2 other criteria sets in real‐life clinical practice scenarios in a relatively small proportion of the patients. However, these criteria could allow earlier classification of a subset of patients with a more severe disease.